Carriers of filaggrin gene (FLG) mutations avoid professional exposure to irritants in adulthood. (28th June 2013) - Bandier, Josefine; Ross‐Hansen, Katrine; Carlsen, Berit C.; Menné, Torkil; Linneberg, Allan; Stender, Steen; Szecsi, Pal B.; Meldgaard, Michael; Thyssen, Jacob P.; Johansen, Jeanne D.
Summary: Background: Loss‐of‐function mutations in the filaggrin gene ( FLG ) are associated with xerosis, atopic dermatitis, and early onset of hand eczema. Irritant exposure is a risk factor for occupational hand eczema, and FLG mutations increase the risk of occupational irritant contact dermatitis on the hands in hospital cohorts. It is unknown whether FLG mutations affect the level of irritant exposure. Objectives: To evaluate whether exposure to occupational irritants was dependent on FLG mutations, atopic dermatitis, and age at hand eczema onset. Methods: Randomly chosen Danish adults completed a questionnaire on general health and occupational exposures. Genotyping for FLG mutations (R501X, 2282del4, and R2447X) and patch testing were performed. Results: Overall, 38.7% of subjects reported present or previous occupational exposure to irritants. Among individuals who reported hand eczema onset before entering their work life, 50.6% (45/89) of FLG non‐mutation carriers became exposed to irritants, as compared with 28.6% (4/14) of heterozygous and 0% (0/6) of homozygous mutation carriers ( p  = 0.006). Avoidance was conspicuous among mutation carriers reporting childhood hand eczema and atopic dermatitis (odds ratio 0.08, 95% confidence interval 0.01–0.65). Conclusions: Carriers of FLG mutations who have had hand eczema onset in childhood avoid occupational exposure to irritants; the association is most marked with homozygous mutation status combined with atopic dermatitis.